2019
DOI: 10.1080/00405000.2019.1624070
|View full text |Cite
|
Sign up to set email alerts
|

Polylactic acid/lyocell fibre as an eco-friendly alternative to polyethylene terephthalate/cotton fibre blended yarns and knitted fabrics

Abstract: This is a repository copy of Polylactic acid/Lyocell fibre as an eco-friendly alternative to Polyethylene terephthalate/Cotton fibre blended yarns and knitted fabrics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
(24 reference statements)
0
14
0
Order By: Relevance
“…PLA fibers have a significant application in packing industry but only around 2% of PLA is used in the form of textile fibers [ 142 ].…”
Section: Pla Applicationsmentioning
confidence: 99%
“…PLA fibers have a significant application in packing industry but only around 2% of PLA is used in the form of textile fibers [ 142 ].…”
Section: Pla Applicationsmentioning
confidence: 99%
“…Jabbar et al 75 and Cao et al 76 revealed the correlation between the blending ratio and the mechanical properties of PLA/lyocell blended yarn. The breaking strength and tenacity of the yarn were found to be increased with the increase of lyocell fiber proportion in the blended yarn, whereas the elongation at break decreased with the increase of lyocell fiber.…”
Section: Ring Spinning Of Pla Yarnmentioning
confidence: 99%
“…2 Due to its high functionalization, glycerol can be transformed into several value-added products ( Table 1), such as lactic acid, [3][4][5] glyceric acid, 6-8 glycolic acid, [9][10][11] oxalic acid, 9,12 dihydroxyacetone, [13][14][15] glyceraldehyde, [16][17][18] 1,2-propanediol, [19][20][21] 1,3-propanediol, 22-24 1-propanol, 25,26 acrylic acid, [27][28][29] acrolein, [30][31][32] syngas, [33][34][35] mono-, di-, tri-glycerides, [36][37][38] triacetin, [39][40][41] glycerol oligomers, 42,43 and polymers. 44 Lactic acid is conventionally used as an acidulant and preservative in the food industry, in the chemical industry 45,46 as raw material for the production of pharmaceuticals, 47 cosmetics, 48 textiles, 49 leather, 50 and, in a fast-growing niche market, as monomer for the biodegradable polymer po...…”
Section: Reactionmentioning
confidence: 99%
“…Due to its high functionalization, glycerol can be transformed into several value‐added products (Table ), such as lactic acid, glyceric acid, glycolic acid, oxalic acid, dihydroxyacetone, glyceraldehyde, 1,2‐propanediol, 1,3‐propanediol, 1‐propanol, acrylic acid, acrolein, syngas, mono‐, di‐, tri‐glycerides, triacetin, glycerol oligomers, and polymers . Lactic acid is conventionally used as an acidulant and preservative in the food industry, in the chemical industry as raw material for the production of pharmaceuticals, cosmetics, textiles, leather, and, in a fast‐growing niche market, as monomer for the biodegradable polymer poly‐(lactic acid) or PLA . Lactic acid can be produced by chemical synthesis or by fermentation from sugars, the latter being the preferred alternative at the industrial level …”
Section: Introductionmentioning
confidence: 99%